2020
DOI: 10.2147/ott.s249046
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dihydroartemisinin Prevents Progression and Metastasis of Head and Neck Squamous Cell Carcinoma by Inhibiting Polarization of Macrophages in Tumor Microenvironment</p>

et al.

Abstract: Background: Polarized M2 macrophages are an important type of tumor-associated macrophage (TAM), with roles in the growth, invasion, and migration of cancer cells in the tumor microenvironment. Dihydroartemisinin (DHA), a traditional Chinese medicine extract, has been shown to inhibit the progression and metastasis of head and neck squamous cell carcinoma (HNSCC); however, the effect of DHA on cancer prevention, and the associated mechanism, has not been investigated in the tumor microenvironment. Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 66 publications
0
28
0
Order By: Relevance
“…As early as 2015, Chan et al reported that EXOs derived from NPC C666-1 cells could markedly enhance the tubulogenesis, migration and invasion of human umbilical vein endothelial cells [ 77 ]. Subsequently, Ferris et al demonstrated that EXOs containing interleukin- 10 (IL-10) and IL-6 secreted by HNSCC and IL-6-dependent inflammatory stimulation resulted in increased angiogenesis [ 78 , 79 ]. EVs derived from HPV (+) and HPV (-) HNSCC cell lines mainly carried urokinase plasminogen activator (uPA).…”
Section: Introductionmentioning
confidence: 99%
“…As early as 2015, Chan et al reported that EXOs derived from NPC C666-1 cells could markedly enhance the tubulogenesis, migration and invasion of human umbilical vein endothelial cells [ 77 ]. Subsequently, Ferris et al demonstrated that EXOs containing interleukin- 10 (IL-10) and IL-6 secreted by HNSCC and IL-6-dependent inflammatory stimulation resulted in increased angiogenesis [ 78 , 79 ]. EVs derived from HPV (+) and HPV (-) HNSCC cell lines mainly carried urokinase plasminogen activator (uPA).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that DHA could inhibit COAD cell viability through regulating cell proliferation and apoptosis [15,42]. e data presented above, in addition to many studies in the literature, indicate that DHA is involved in regulating the TME of cancer [16,26]. However, there is no publicly available information about the role of DHA in the TME of COAD.…”
Section: Discussionmentioning
confidence: 90%
“…DHA has potential antitumor therapeutic effects across human cancers through inhibition of cancer cell proliferation, migration, and invasion capabilities. DHA was proposed to regulate the TME in head and neck cancer, breast cancer, and melanoma [ 16 , 25 , 26 ]. However, the effect of DHA in the TME of COAD has not been previously described.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found out that the promoter of miR‐21 harbors multiple STAT3 binding sites and STAT3 activation is required for induction of miR‐21 transcription (Iliopoulos et al, 2010). And it is also found that STAT3 is activated during M2 polarization of macrophages (Chen et al, 2020). In our previous study, we found that arsenite induced increase of miR‐21 by the IL‐6/STAT3 pathway (Lu et al, 2015).…”
Section: Discussionmentioning
confidence: 98%